Liver stiffness assessment with tagged MRI of cardiac‐induced liver motion in cirrhosis patients. Issue 5 (23rd September 2013) - Chung, Sohae; Kim, Kyoung‐Eun; Park, Mi‐Suk; Bhagavatula, Sharath; Babb, James; Axel, Leon
Abstract : Purpose: To assess liver stiffness using magnetization‐tagged magnetic resonance imaging (MRI) to measure the cardiac‐induced motion in the liver of cirrhosis patients with known Child‐Pugh scores. Materials and Methods: Tagged MRI was performed using a 3T MR scanner on 52 cirrhosis patients classified into two groups: liver cirrhosis with Child‐Pugh A (LCA; n = 39) and liver cirrhosis with Child‐Pugh B or C (LCBC; n = 13). We also included 19 healthy controls. Tagged images were acquired encompassing both the liver and the heart. The corresponding displacement and strains were calculated using a Gabor filter bank. The maximum displacement (MaxDisp) was found over the cardiac cycle, as well as the local maximum P1 (MaxP1) and minimum P2 strains (MinP2). Group comparisons were made without and with adjustment for age and gender. Results: In control, LCA, and LCBC groups, the MaxDisp was 3.98 ± 0.88 mm, 2.52 ± 0.73 mm, and 1.86 ± 0.77 mm; the MaxP1 was 0.10 ± 0.02, 0.04 ± 0.01, and 0.02 ± 0.01; and the MinP2 was −0.08 ± 0.01, −0.05 ± 0.02, and −0.03 ± 0.01, respectively. Statistically significant differences were found between groups ( P < 0.05 for all). Conclusion: This method measures cardiac‐induced liver motion and deformation to assess liver stiffness. Significant differences were found in our stiffness measures between control, LCA, and LCBC groups, with more severe disease being associated with greater stiffness.J. Magn. Reson. Imaging 2014;39:1301–1307 . ©2013 Wiley Periodicals, Inc .